Portfolio inertia and stock market fluctuations - Yannis Bilias; Dimitris Georgarakos; Michael Haliassos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
Several recent studies have addressed household participation in the stock market, but relatively few have focused on household stock trading behavior. Household trading is important for the stock market, as households own more than 40% of the NYSE capitalization directly and can also influence trading patterns of institutional investors by adjusting their indirect stock holdings. Existing studies based on administrative data offer conflicting results. Discount brokerage data show excessive trading to the detriment of stockholders, while data on retirement accounts indicate extreme inactivity. This paper uses data representative of the population to document the extent of household portfolio inertia and to link it to household characteristics and to stock market movements. We document considerable portfolio inertia, as regards both changing stockholding participation status and trading stocks, and find that specific household characteristics contribute to the tendency to exhibit such inertia. Although our findings suggest some dependence of trading directly-held equity through brokerage accounts on the performance of the stock market index, they do not indicate that the recent expansion in the stockholder base and the experience of the stock market downswing have significantly altered the overall propensity of households to trade in stocks or to switch participation status in a way that could contribute to stock market instability.
urn:nbn:de:hebis:30-27731
Keywords: G11; E21; 330; Stockholding; Portfolio Inertia; Stock Trading; Household Portfolios